Derrida and Queer Theory - Hite, Christian (punctum books, 2017)
Coming from behind (derrière)-how else to describe a volume called "Derrida and Queer Theory"? - as if arriving late to the party, or, indeed, after the party is already over. After all, we already have Deleuze and Queer Theory and, of course, Saint Foucault. And judging by Annamarie Jagose's Queer Theory: An Introduction, in which there is not a single mention of "Derrida" (or "deconstruction") - even in the sub-chapter titled "The Post-Structuralist Context of Queer" - one would think that Derrida was not only late to the party, but was never there at all. This untimely volume, then, with wide-ranging essays from key thinkers in the field, addresses, among other things, what could be called the disavowed debt to "Derrida" in canonical "queer theory."